We want to factor the expression x - a, in such a way that we have one factor written as:
(√x - √a)
We will find that the factorized expression is:
(√x - √a)*(√x + √a)
Here we need to remember two things:
First, (√x)^2 = √(x^2) = x
also:
(x^2 - y^2) = (x + y)*(x - y)
Now, using the first property, we can rewrite our original expression as:
(x - a) = ( (√x)^2 - (√a)^2)
Now, using the second property, we can rewrite it as:
( (√x)^2 - (√a)^2) = (√x - √a)*(√x + √a)
Then we have:
(x - a) = (√x - √a)*(√x + √a)
Thus, we have factorized (x - a) in such a way that one of the factors is equal to (√x - √a)
If you want to learn more, you can read:
https://brainly.com/question/19386208